Monitoring the delicate operations of surgical robots via ultra-sensitive ionic electronic skin. Issue 12 (21st October 2022) - Wei, Danyang; Guo, Jiajie; Qiu, Yuqi; Liu, Shaoyu; Mao, Jiangyan; Liu, Yutian; Chen, Zhenbing; Wu, Hao; Yin, Zhouping
Abstract: The arrival of surgical robots in high-end medical equipment is a landmark, and the realization of tactile sensation a major challenge in this important cutting-edge research field. Aiming to address this issue, we present ultra-sensitive ionic electronic skin in the form of flexible capacitive pressure sensors, which incorporate multistage bionic microstructures in ion gels for the purpose of monitoring the delicate operations of surgical robots. Significantly, the ionic skin exhibits an ultra-high sensitivity of 9484.3 kPa −1 (<15 kPa), and the sensitivity remains higher than 235 kPa −1 in the wide range of 15–155 kPa. The device has also achieved a detection limit as low as 0.12 Pa or, equivalently, 0.31 mg, fast response within 24 ms, and high robustness (loading/unloading for 5000 cycles without fatigue). The sensor facilitates the challenging task of tele-operated robotic threading, which exceeds the human tactile perception limit when threading a needle. We have also confirmed that ionic skin can be used in robot-assisted invasive surgery, such as incision/resection of tissues and suturing of wounds, providing tactile information to surgeons to improve operation success rates. The flexible ionic skin is capable of conforming to the various shapes of robotic manipulators, thus has great promise for applications in robotic dexterous manipulation, prosthetics and human–machine interfaces. Abstract : An ultra-sensitive ionic electronic skin is utilized for robot-assisted invasive surgery, such as incision/resection of tissues and suture of wound, to provide tactile information to surgeons to improve the operation success rates.